Effects of new over‐the‐counter periodontal ointment‐containing applicator with single‐tuft brush on cytokine levels in gingival crevicular fluid during supportive periodontal therapy phase: a randomized double‐blind clinical trial. (6th August 2015) - Takeuchi‐Hatanaka, K.; Yasuda, T.; Naruishi, K.; Katsuragi‐Fuke, K.; Inubushi, J.; Ootsuki, H.; Maeda, H.; Takashiba, S.
Abstract : Background and Objective: The biochemical effects of an over‐the‐counter (OTC) medication were studied, which consists of a single‐tuft brush containing cetylpyridinium chloride as a bactericidal agent, dipotassium glycyrrhizate as an anti‐inflammatory drug and allantoin as a promoter of cell proliferation and wound healing, for delivery to hardly brushed sites. Material and Methods: This randomized controlled double‐blind study was performed in 61 subjects with chronic periodontitis in supportive periodontal therapy phase (test group: n  = 27; placebo group: n  = 28; dropout: n  = 6). The OTC medication was self‐applied twice a day for 12 wk to two molars with probing pocket depths of 4–6 mm. Biochemical indicators were evaluated at baseline and 12 wk using the suspension array system for eight cytokines and chemokines (interleukin [IL]‐1β, IL‐1ra, IL‐4, IL‐6, IL‐8, IL‐10, monocyte chemoattractant protein‐1 and tumor necrosis factor [TNF]‐α) in gingival crevicular fluid. Results: The levels of IL‐1β, IL‐6, IL‐8 and TNF‐α remained significantly lower in the test group compared to the placebo group. In the placebo group, when the probing pocket depth at baseline was 4 mm, IL‐1β increased, particularly in the second molar tooth, and the greatest increase was seen when PPD at baseline was 5–6 mm. In the test group, IL‐1β decreased markedly in cases with furcation involvement and low bleeding on probing at baseline. In both groups, IL‐1β, IL‐6 and TNF‐α were closely correlated with each other. Conclusion: This OTC medication is biochemically effective for steady chronic periodontitis in the supportive periodontal therapy phase.